Improved Tolerance to Root Rot and Bacterial Blights in Kidney Bean: Registration of 'Talon' Dark Red Kidney and 'Rosie' Light Red Kidney. Issue 1 (1st September 2016) - Osorno, Juan M.; Grafton, Kenneth F.; Vander Wal, Albert J.; Kloberdanz, Michael; Schroder, Stephan; Vasquez, Jose E.; Ghising, Kiran; Pasche, Julie S.
Abstract : 'Talon' dark red kidney (Reg. No. CV‐314, PI 674157; PVP #201500067) and 'Rosie' light red kidney (Reg. No. CV‐313, PI 674156; PVP #201500066) are two new kidney bean ( Phaseolus vulgaris L.) cultivars developed by the dry bean breeding program at North Dakota State University and released by the North Dakota Agricultural Experimental Station. Talon has medium‐early maturity, while Rosie is late maturing. Both Talon and Rosie are high‐yielding cultivars with commercially acceptable seed size, shape, and appearance. Both Talon and Rosie were tested between 2006 and 2015 across 24 environments in Minnesota and North Dakota and have shown a superior seed yield compared with cultivars commonly grown in the region. Averaged across all environments, Talon produced 153 and 359 kg ha −1 more than 'Montcalm' and 'Redhawk', respectively. Rosie produced 991, 355, and 222 kg ha −1 more than 'CELRK', 'Foxfire', and 'Pink Panther', respectively. In comparison with the commercial checks, both Talon and Rosie displayed intermediate resistance to the root rot complex under field conditions in Minnesota. In addition, Talon displayed intermediate resistance and Rosie was rated as resistant to both common bacterial blight [caused by Xanthomonas axonopodis pv. phaseoli (Smith) Vauterin et al.] and halo blight [caused by Pseudomonas syringae pv. phaseolicola (Burkholder) Young et al.] in the field. The improved levels of resistance to both root rots and bacterial diseases combined with the superior agronomic performance over kidney bean cultivars commonly grown in the United States suggest that Rosie and Talon have the potential to be among the most important kidney cultivars in the United States.